Civil appeals - Brown, Donald J. M. (Thomson Reuters, 2019)
"This unique publication is an in-depth presentation of the law, regarding issues that arise in the appeal process before the appellate courts of Canada – scope information (Thomson Reuters Westlaw Canada).
Book Title: Civil appeals